Iridium‐Catalysed Reductive Deoxygenation of Ketones with Formic Acid as Traceless Hydride Donor. Issue 23 (20th October 2020) - Yang, Zhiheng; Zhu, Xueya; Yang, Shiyi; Cheng, Weiyan; Zhang, Xiaojian; Yang, Zhanhui
Abstract: An iridium‐catalysed deoxygenation of ketones and aldehydes is achieved, with formic acid as hydride donor and water as co‐solvent. At low catalyst loading, a number of 4‐( N, N ‐disubstituted amino) aryl ketones are readily deoxygenated in excellent yields and chemoselectivity. Numerous functional groups, especially phenolic and alcoholic hydroxyls, secondary amine, carboxylic acid, and alkyl chloride, are well tolerable. Geminally dideuterated alkanes are obtained with up to 90% D incorporation, when DCO2 D and D2 O are used in place of their hydrogenative counterparts. The activating 4‐( N, N ‐disubstituted amino)aryl groups have been demonstrated to undergo a variety of useful transformations. The deoxygenative deuterations have been used to prepare a deuterated drug molecule Chlorambucil‐4, 4‐ d2 . Abstract :